Making European Citizens
XI, 270 p.
Keywords: Making European Citizens examines the forms of transnational citizenship developing in Europe. Active citizenship involves more than simply voting. Achieving mobilization at a transnational level may involve new democratic techniques and skills. The volume explores how far European citizens have acquired the requisite methods and qualities.